Survey of undiagnosed airflow limitation among cardiac and diabetic patients in a Nigerian teaching hospital - Ayodele A Akinremi; Kafayat K Sobande; Talhatu K Hamzat (Wolters Kluwer Medknow Publications, 2020)
Background Airflow limitation is associated with all-cause mortality and could worsen treatment outcomes in chronic diseases. In resource-limited countries, where availability of spirometry facilities poses a major challenge, the magnitude of airflow limitation among patients with chronic diseases is unknown. Such information may justify the need for routine lung function screening, early detection, and management of airflow impairment among this population. Objective This study aims to estimate the magnitude of airflow limitation among patients attending endocrinology and cardiology clinics in a tertiary healthcare facility in south-western Nigeria. Patients and methods A cross-sectional survey design study was performed, involving individual with diabetes and hypertension who were recruited from the outpatient unit of the hospital. A handheld digital spirometer was used to measure lung function indices. Data were analyzed using descriptive statistics of mean, SD, frequencies, and percentages. c2 test was used to test for difference in proportions between sexes and patient groups. Results A total of 124 (90 females and 34 males) patients, comprising of 53 patients with diabetes, 67 with hypertension, and four with both diabetes and hypertension, participated in this study. Overall, 91 (73%) participants had airflow limitation: 52 (78%) of 67 hypertensive patients and 36 (68%) of the 53 patients with diabetes. Airflow limitation was significantly higher among men (94%) than women (66%). Severity of airflow limitation was as follows: 61 mild cases, 28 moderate, and two severe cases, which were undetected and untreated among the study population. Conclusion Airflow limitation is common among the study population. Strategies aimed at early detection through routine lung function screening may be beneficial.